PENINGKATAN MINAT BACA DI KALANGAN ANAK USIA DINI DI SEKOLAH ALTERNATIF ANAK JALANAN (SAAJA) - Mariska, Anis; Adiningsih, Anisyah; Anindyta, Claudya; Ratri, Pupung Dianing; Anggraini, Yunia Puspita; Safitri, Dini (Jurnal Terapan Abdimas, 2020)
Abstract. In major cities in Indonesia there have been many formal schools established in terms of developing children's education at an early age, so that the quality and quality of children in big cities is good. However, formal schools require considerable costs so that they are still difficult to reach by underprivileged families. Concern for underprivileged families inspired the establishment of alternative schools in order to reach education at an early age as an example of which in SAAJA these children experienced a number of problems including lack of awareness of reading interest in each individual, limited human resources, and lack of facilities, especially children's reading books. The purpose of this service activity is to foster reading interest in early childhood at SAAJA. The method used is the Storytelling Method and the Learning While Playing Method. As a result of this activity, participants actively read children's books in addition they are able to sharpen their memory to remember what they have told.Abstrak. Di kota-kota besar di Indonesia telah banyak berdiri sekolah formal dalam hal pengembangan pendidikan anak pada usia dini, Sehingga mutu dan kualitas anak-anak dikota besar sudah bagus. Namun, sekolah formal memerlukan biaya yang cukup besar sehingga masih sulit dijangkau oleh keluarga prasejahtera. Kepedulian terhadap keluarga prasejahteramemberikan inspirasi untukmendirikan sekolah alternatif demi menjangkau pendidikan pada usia dini sebagai contoh salah satunya adalah di SAAJA anak-anak tersebut mengalami sejumlah permasalahan diantaranya yaitu kurangnya kesadaran minat baca pada masing-masing individu, keterbatasan sumber daya manusia, dan minimnya fasilitas, terutama buku-buku bacaan anak. Tujuan kegiatan pengabdian ini dapat menumbuhkan minat baca pada anak usia dini di SAAJA, Metode yang digunakan adalahMetode Storytelling dan Metode Bermain Sambil Belajar, Hasil kegiatan ini, peserta aktif membaca buku anak-anak selain itu mereka mampu mengasah daya ingat untuk mengingat apa yang telah diceritakan.